PERANCANGAN KEMASAN PRODUK KERUPUK DENGAN METODE QUALITY FUNCTION DEPLOYMEN PADA UMKM KERUPUK TERUNG - Kurniawan, Adi; Al Ma'ruf, Hidayat; Alifah, Umi; Riyanti, Ririn (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to redesign the packaging of eggplant crackers produced by Ibu Dashroah's Eggplant Crackers SME in Pekalongan to meet consumer needs and increase product competitiveness. The method used is Quality Function Deployment (QFD) with a House of Quality (HOQ) approach, which includes identifying the Voice of Customer (VOC) through a valid and reliable questionnaire, collecting primary data from observations and interviews, and analyzing packaging technical priorities. The results of the study identified six main attributes of consumer needs, such as attractive design, practical packaging, and product quality protection. The HOQ analysis showed that packaging size (relative importance 22.5) and packaging material (21.4) were the highest priorities, followed by information placement, shape, color, and packaging weight. Therefore, a new functional, informative, and visually appealing packaging design was proposed to support increased sales for SMEs.